Association of magnesium intake with sleep duration and sleep quality: findings from the CARDIA study. Issue 4 (20th November 2021) - Zhang, Yijia; Chen, Cheng; Lu, Liping; Knutson, Kristen L; Carnethon, Mercedes R; Fly, Alyce D; Luo, Juhua; Haas, David M; Shikany, James M; Kahe, Ka
Abstract: Study Objectives: As an antagonist of calcium (Ca), magnesium (Mg) has been implicated in the regulation of sleep. We aimed to examine the longitudinal associations of Mg intake and Ca-to-Mg intake ratio (Ca:Mg) with sleep quality and duration. Methods: The study sample consisted of 3, 964 participants from the Coronary Artery Risk Development in Young Adults (CARDIA) study. Dietary and supplementary intake of Mg were obtained using the CARDIA Dietary History at baseline (1985–1986), exam years 7 and 20. Self-reported sleep outcomes were measured at years 15 and 20. Sleep quality was rating from 1 (very good) to 5 (very bad). We categorized sleep duration to <7, 7–9, and >9 h. Generalized estimating equation was used to examine the associations of interest as repeated measures at the two time points. Results: After adjustment for potential confounders, Mg intake was borderline associated with better sleep quality [highest quartile (Q4) vs. intake quartile (Q1): odds ratio (OR) = 1.23; 95% CI = 0.999, 1.50, p trend = 0.051]. Participants in Q4 were also less likely to have short sleep (<7 h) compared to those in Q1 (OR = 0.64; 95% CI = 0.51, 0.81, p trend = 0.012). The observed association with short sleep persisted among participants without depressive disorders (Q4 vs. Q1: OR = 0.64; 95% CI = 0.49, 0.82, p trend < 0.001), but not among individuals with depressive disorder. Ca:Mg was not associated with either outcomes, regardless of depression status. Conclusions: Mg intake was associated with both sleep outcomes in this longitudinal analysis. Randomized controlled trials with objective measures of sleep are warranted to establish the potential causal inference.